Developing an English Language School Management Course: Curriculum Innovation and Entrepreneurial Opportunities at Universitas Negeri Makassar - Korompot, Chairil Anwar; Fauzan, Muhammad Miftah; Nur, Sahril (VELES Voices of English Language Education Society, 2023)
This paper is based on a systematic literature review conducted to justify the introduction of a new course, 'English Language School Management' (ELSM), in the English Language Education Study Program (ELESP) at Universitas Negeri Makassar, Indonesia. The literature review involved a detailed analysis of academic sources relevant to English language education and management, identifying gaps in current academic discourse and practical educational needs in the post-Covid-19 context. Prompted by the implementation of the Merdeka Belajar Kampus Merdeka program, which necessitated curriculum revision, ELSM was developed. This course aims to provide ELESP students with critical insights into the operation and management of English language schools. These institutions are vital in non-formal education, as underutilized partners in teacher training programs, and as potential employment and entrepreneurial opportunities for graduates. The introduction of ELSM addresses a notable lack of focus on English language schools within Indonesian academic circles, despite their popularity and significant educational contributions. The development of this course is expected to enhance ELESP students' awareness of both the potential and challenges faced by English language schools, especially in the post-pandemic era.